A Cost-effectiveness Analysis of Aspirin versus Oral Anticoagulants after Acute Myocardial Infarction in Italy - Gianetti, Jacopo; Gensini, Gianfranco; Caterina, Raffaele De (Thrombosis and Haemostasis, 1998)
Aims. The recent publication of two large trials of secondary prevention of coronary artery disease with oral anticoagulants (WARIS and ASPECT) has caused a revival of the interest for this antithrombotic therapy in a clinical setting where the use of aspirin is common medical practice. Despite this, the preferential use of aspirin has been supported by an American cost-effectiveness analysis (JAMA 1995; 273: 965). Methods and Results. Using the same parameters used in that analysis and incidence of events from the Antiplatelet Trialists Collaboration and the ASPECT study, we re-evaluated the economic odds in favor of aspirin or oral anticoagulants in the Italian Health System, which differs significantly in cost allocation from the United States system and is, conversely, similar to other European settings. Recalculated costs associated with each therapy were 2,150 ECU/ patient/year for oral anticoagulants and 2,187 ECU/patient/year for aspirin. In our analysis, the higher costs of oral anticoagulants versus aspirin due to a moderate excess of bleeding (about 10 ECU/ patient/year) and the monitoring of therapy (168 ECU/ patient/year) are more than offset by an alleged savings for recurrent ischemic syndromes and interventional procedures (249 ECU/ patient/year). Conclusions. Preference of aspirin vs. oral anticoagulants in a pharmaco-economical perspective is highly dependent on the geographical situation whereupon calculations are based. On a pure cost-effectiveness basis, and in the absence of data of direct comparisons between aspirin alone versus I.N.R.-adjusted oral anticoagulants, the latter are not more expensive than aspirin in Italy and, by cost comparisons, in other European countries in the setting of post-myocardial infarction.